2019
DOI: 10.1111/ddi.12990
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic, synergistic and direct effects of land use and climate on Prairie wetland ecosystems: Ghosts of the past or present?

Abstract: Aim Wetland loss and degradation threaten biodiversity to an extent greater than most ecosystems. Science‐supported responses require understanding of interacting effects of land use and climate change on wetland biodiversity. Location Alberta, Canada. Methods We evaluated how current climate, climate change (as a ghost of the past), land use and wetland water quality relate to aquatic macroinvertebrates and birds. Results Climatic relationships and climate–land use interactions were observed on chironomid abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 99 publications
(163 reference statements)
0
10
1
Order By: Relevance
“…These findings contrast with previous research elsewhere in the Great Plains testing the "climate bottleneck hypothesis" that found that grassland breeding bird abundance did not significantly change in response to changes in precipitation (Wiens, 1973;Zimmerman, 1992), with the important caveat that our study areas differed in their proximity to riparian corridors and therefore flooding potential. Our findings also contrast with a pattern of increasing bird abundance with increasing precipitation for wetland bird species elsewhere in the Great Plains (Mantyka-Pringle et al, 2019). Dickcissel abundance decreased with increased precipitation during the breeding season but not the non-breeding season (when they are away), implying that negative effects of increased precipitation on dickcissels stem from direct effects during the breeding season, such as emigration due to heavy precipitation and related extreme events including flooding and summer hailstorms.…”
Section: Discussion Dickcissel Relationships With Precipitation and Grassland Managementcontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings contrast with previous research elsewhere in the Great Plains testing the "climate bottleneck hypothesis" that found that grassland breeding bird abundance did not significantly change in response to changes in precipitation (Wiens, 1973;Zimmerman, 1992), with the important caveat that our study areas differed in their proximity to riparian corridors and therefore flooding potential. Our findings also contrast with a pattern of increasing bird abundance with increasing precipitation for wetland bird species elsewhere in the Great Plains (Mantyka-Pringle et al, 2019). Dickcissel abundance decreased with increased precipitation during the breeding season but not the non-breeding season (when they are away), implying that negative effects of increased precipitation on dickcissels stem from direct effects during the breeding season, such as emigration due to heavy precipitation and related extreme events including flooding and summer hailstorms.…”
Section: Discussion Dickcissel Relationships With Precipitation and Grassland Managementcontrasting
confidence: 99%
“…Broaderscale climate effects can also influence dickcissels' settlement decisions (Jensen and Cully, 2005), for example if dickcissels concentrate in the southern part of their breeding range in wetter years and in the northern part of their range in drier years or vice versa. Climate change may thus influence bird species on a broader scale, as geographic shifts in climate envelope may sometimes outweigh effects of local land management (Barbet-Massin et al, 2012;Sohl, 2014;Mantyka-Pringle et al, 2019). Other factors not captured in this study may also influence breeding bird populations, such as carry-over effects, which recent students have suggested are widespread and important in many bird species (Harrison et al, 2011;O'Connor et al, 2014) and can be sex-and age-specific (Saino et al, 2017;López-Calderón et al, 2019).…”
Section: Discussion Dickcissel Relationships With Precipitation and Grassland Managementmentioning
confidence: 90%
“…Our results suggest that climate change projections of increased frequency of extreme climate events may generate large, and perhaps distinct, effects on apparent LRS of species across their range. In the prairies where current warmer, wetter conditions associated with climate change appear to be benefiting some species 70 , climate scenarios are forecasting more frequent and severe drought conditions and widespread drying of ponds 71,72 , which our results suggest could negatively affect the fitness of terrestrial species. Such effects will not only occur via habitat loss, but also through the loss of aquatic food resources for a variety of species.…”
Section: Discussionmentioning
confidence: 80%
“…Broaderscale climate effects can also influence dickcissels' settlement decisions (Jensen and Cully, 2005), for example if dickcissels concentrate in the southern part of their breeding range in wetter years and in the northern part of their range in drier years or vice versa. Climate change may thus influence bird species on a broader scale, as geographic shifts in climate envelope may sometimes outweigh effects of local land management (Barbet-Massin et al, 2012;Sohl, 2014;Mantyka-Pringle et al, 2019). Other factors not captured in this study may also influence breeding bird populations, such as carry-over effects, which recent students have suggested are widespread and important in many bird species and can be sex-and age-specific (Saino et al, 2017;López-Calderón et al, 2019).…”
Section: Discussion Dickcissel Relationships With Precipitation and Grassland Managementmentioning
confidence: 91%